Seattle Neighborhoods and Crime Survey, 2002-2003 - Matsueda, Ross L. ([Verlag nicht ermittelbar], 2010)
The objective of the Seattle Neighborhoods and Crime Survey (SNCS) was to test multilevel theories of neighborhood social organization and criminal violence. It was funded by the National Science Foundation (SES-0004324), and the National Consortium on Violence Research (SBR-9513040). Using the concept of differential neighborhood organization, the investigators posited that neighborhood crime is a function of informal social control against crime and informal organization in favor of crime. Informal neighborhood control against crime consists of neighborhood attachment, social capital, and collective efficacy. The study tested the hypothesis that individual social ties are explained by a rational choice model, which in turn produces neighborhood social capital that can be used to achieve collective goals. It also tested the hypothesis that neighborhoods rich in social capital had greater collective efficacy, which in turn, helped produce safe neighborhoods. Organization in favor of crime consists of violent codes of the street. The study tested the hypothesis that residents from disadvantaged neighborhoods tend to distrust police and other agents of conventional institutions, and consequently are more likely to participate in street culture, in which violence is a way of obtaining street credibility and status, as well as resolving disputes. The project has also examined dimensions of neighboring, and the causes and consequences of fear of crime. The study used a telephone survey of households within all 123 census tracts in the city of Seattle, WA, conducted in 2002-2003. The sampling frame was designed by investigators at the University of Washington, with three objectives in mind: (a) to gain a random sample of households within each of 123 census tracts; (b) to obtain a disproportionate number of racial and ethnic minorities using an ethnic oversample; and (c) to obtain a replication sample of Terrance Miethe's 1990 victimization survey in 100 Seattle neighborhoods [Testing Theories of Criminality and Victimization in Seattle, 1960-1990]. Specific samples were drawn by Genesys, a sampling firm in Philadelphia, PA, using a constantly-updated compilation of white pages. Telephone interviews were conducted by the Social and Behavioral Research Institute at California State University, San Marcos, using computer-assisted telephone interviewing (CATI) technology. Respondents were asked about household demographics, such as race, gender, residential mobility, age distribution of the household, and income, their perceptions and assessments of their neighborhoods (including safety, disorder, and crime), neighbors, and relations with police. A variety of questions about neighboring were asked, including social capital (intergenerational closure, reciprocated exchange, and participation in neighborhood associations), attachment to their neighborhood, and collective efficacy (child-centered social control). Respondents were asked about routine activities including taking steps to protect their homes, spending time in bars and nightclubs, and leaving their home unattended. Questions about fear of crime included personal fear as well as altruistic fear for other members of the household, and questions about racial attitudes included residential preferences by race composition of the neighborhood. A victimization inventory modeled after the National Crime Victimization Survey was used for burglary, vandalism, stolen property, violence, and robbery. Demographic information includes age, race, sex, education, martial status, household income, whether respondent was a student, employment status, religious affiliation, approximate value of home, monthly rent including utilities, residence history in the last five years, whether respondent was born in the Unites States, and number of people currently living in the respondent's household.